Teaching Secondary School Students with Learning Disabilities to Cope in Preparation for College. Issue 1 (4th March 2019) - Mazher, Waseem
Abstract: The purpose of this article is to explore how to teach secondary school students with learning disabilities (LD) to cope effectively, so they may develop self-determination (independence) skills in secondary school and beyond, in college. Teachers need to know about coping and what makes it effective in school as well as in a college context. I describe psychological concerns and methods of teaching that can allow students with LD to cope effectively in secondary school and in college.